1980
DOI: 10.1007/bf01245221
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal pattern of adrenergic metabolites in urine of small for gestational age and preterm infants

Abstract: Catecholamines (DA, NE, E), methoxyamines (MT, NMN, MN), DOPA and DOPAC were studied in urine of term small for gestational age infants (SGA) and preterm with appropriate birthweights for gestational age (PT) during the first ten days of life. Results were compared to values obtained for full term infants (FT). As a whole no deficit in urine catecholamines was observed in either group of SGA and PT neonates suggesting that capacities to synthesize catecholamines are already developed at birth. Furthermore, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0
2

Year Published

1982
1982
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 26 publications
2
6
0
2
Order By: Relevance
“…In neonatal hypoglycemia, there is no change of blood concentration of free fatty acids [22] and ketone bodies [23] suggesting a defective reactive compensatoryregulation which may be related to abnormal secretion of catecholamines [24]. This re duced production of lipid substrates is not explained by a defect of carnitine and/or betaoxidation [25], We have shown that the oral administration of lipids (mainly with me dium-chain triglycerides.…”
Section: Lipids and Glueoneogenesismentioning
confidence: 99%
“…In neonatal hypoglycemia, there is no change of blood concentration of free fatty acids [22] and ketone bodies [23] suggesting a defective reactive compensatoryregulation which may be related to abnormal secretion of catecholamines [24]. This re duced production of lipid substrates is not explained by a defect of carnitine and/or betaoxidation [25], We have shown that the oral administration of lipids (mainly with me dium-chain triglycerides.…”
Section: Lipids and Glueoneogenesismentioning
confidence: 99%
“…Although the CAT response has been ex amined at term gestation both in humans and animals, only a few studies have measured CAT release in the preterm human infant [6][7][8], However, these studies have included a mixed group of infants mostly greater than 29 weeks gestation, and have included acidotic and asphyxiated newborns [6][7][8]. The pur pose of the present study was to examine the ability of the very premature infants to mount a CAT response at birth in the absence of asphyxia and to compare their response with that observed in near-term healthy newborn infants.…”
Section: Introductionmentioning
confidence: 99%
“…This find ing may indicate relatively high dopamine and NE turnover in preterm infants, but the high plasma levels of DOPAC and DHPG may as well relate to a low urinary excretion 299 rate of the metabolites. Previous data rather support the latter explanation: high plasma levels of catecholamine metabolites in pre term infants have been documented [16], but the urinary excretion rate of DOPAC has been found to be low [ 13]. Moreover, preterm infants have immature renal function both with respect to glomerular and tubular func tion [27,28], which could lead to a low clear ance rate of catecholamine metabolites.…”
Section: Discussionmentioning
confidence: 73%
“…Preterm infants tend to have lower cord blood E and NE levels than term infants [3,5], and they have responded with less catechol amine secretion during asphyxia compared with term infants [3], suggesting that the sym- pathoadrenal system might not be completely developed before term [9], Studies on cate cholamine metabolism after birth have mainly measured urinary excretion of cate cholamines [10][11][12][13][14], Studies of plasma cate cholamines and their metabolites during the early postnatal period are quite limited [1,…”
Section: Introductionmentioning
confidence: 99%